Geochemistry of Hydrothermal Fluids From the E2-Segment of the East Scotia Ridge: Magmatic Input, Reaction Zone Processes, Fluid Mixing Regimes and Bioenergetic Landscapes - Pereira, Samuel I.; Diehl, Alexander; McDermott, Jill M.; Pape, Thomas; Klose, Lukas; Strauss, Harald; Bohrmann, Gerhard; Bach, Wolfgang (Frontiers in Marine Science, 2022)
The compositions of hydrothermal fluids in back-arc basins (BABs) can be affected by the influx of magmatic fluids into systems that are dominated by reactions between basement rocks and seawater-derived fluids. The East Scotia Ridge (ESR) in the Scotia Sea hosts such hydrothermal systems where the role of magmatic fluid influx has not yet been addressed. During expedition PS119 in 2019, three chimneys were sampled from the E2 segment. These samples were analysed for their chemical and isotopic composition along with fluid inclusions in corresponding precipitates. Our data provide evidence for the temporal evolution of hydrothermal fluids in this remote back-arc system. Salinity variations in anhydrite-hosted fluid inclusions indicate that phase separation takes place in the subseafloor. Moderate-temperature (<53°C) fluids from the newly discovered E2-West hydrothermal vent field and high-temperature (>320°C) fluids from the E2-South area were sampled. Depletions in fluid-mobile elements, ΣREE and low δ18OH2O show that the basement in this root zone has been leached since the previous sampling in 2010. The results indicate that high-temperature fluid-rock interactions are key in setting the composition of the fluids with cation-to-chloride ratios suggesting a common root zone for both vent sites. The concentrations of dissolved gases provide new insights in the connection between magmatic degassing and its influence on endmember vent fluid composition. Specifically, stable isotope (O, H) data and elevated CO2 concentrations point to a minor influx of magmatic vapour. Stable sulphur isotopes provide no evidence for SO2 disproportionation suggesting a H2O-CO2 dominated nature of these vapours. The concentrations of conservative elements in the E2-W fluid reflects subseafloor mixing between E2-S endmember fluid and seawater. In contrast, non-conservative behaviour, and depletion of Fe, H2, and H2S point to a combination of sub-surface abiotic and biotic reactions affecting these fluids. Similarly, E2-W fluids show evidence for H2S and CH4 being metabolized in the subseafloor. Thermodynamic computations confirm that the E2 system is dominated by sulphide oxidation as a major catabolic pathway. Our results indicate that the conditions at E2 are favourable to hosting a robust subseafloor biosphere.